MENCIPTAKAN PEMBELAJARAN MATEMATIKA YANG EFEKTIF DALAM PEMECAHAN MASALAH MATEMATIKA DENGAN MODEL PEMBELAJARAN PROBLEM POSING - Ngaeni, Evi Nur; Saefudin, Abdul Aziz (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The learning process is a process that contains reciprocal relationships between teachers and students, which takes place in an educational situation to achieve a particular goal. This interaction or mutual relationship between teachers and students is a key requirement for the process. What we are seeing in schools, teachers are too active in the learning process, while students are made passive, so the interaction between teachers and students in the learning process is not effective. To create effective mathematics learning requires appropriate learning models to solve and solve problems related to mathematics learning. Problem solving is one of the goals of learning mathematics. Learning math so that it can stimulate the development of ability. One strategy that can be used to create effective learning and. Problem posing decline on problem-making by students based on certain criteria, namely the solution of pre-suggestion (for question), in the solution pose (break the question), post a solution pose (similar problems)